Physical Stability Evaluation of Cassava Leaf Aqueous Extract Emulgel (Manihot esculenta) - Rahman, Havizur; Sari, Indah; Sani, Fathnur (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Cassava leaves contain various secondary metabolites such as flavonoids and saponins that can be used as anti-inflammatory and antibacterial.This study aims to determine the physical stability of cassava leaf extract emulgel (Manihot esculenta), which can be used as an anti-inflammatory. Emulgel was made in 3 formulas with variations in the concentration of cassava leaf extract, namely 2.5%, 5%, and 7.5%. Emulgel stability tests include organoleptic tests, homogeneity, viscosity, dispersibility, adhesion, and pH. Stability testing using the cycling test method for 12 days of storage at temperatures 4oC and 40oC. This study showed cassava leaf extract can be formulated as emulgel and has good stability after storage at extreme temperatures for 12 days. Emulgel formulations from cassava leaf extract have good stability and can be anti-inflammatory.